Konsep Ellected Official Sebagai Syarat Pencalonanan Presiden dan Wakil Presiden Perspektif Maslahah - Hafifulloh, Mukhtadin Fajri; Setiawan, Agus (JURNAL HUKUM PELITA, 2024)
Constitutional Court Decision Number: 90/PUU-XXI/2023 is a decision relating to the requirements for presidential and vice presidential candidates. The basis for filing the lawsuit is Law Number 7 of 2017 concerning General Elections. The results of this decision state that the age limit for presidential and vice presidential candidates is 40 years or that they are currently occupying positions elected through general elections (Elected Official). Literature research with researchers utilizing the Constitutional Court Decision as a primary source, and secondary data sources using books and journals. Research shows that the concept of Elected Official in the Constitutional Court decision refers to the judge's view. According to Constitutional Justices Enny Nurbaningsih and Daniel Yusmic P. Foekh, what is meant by officials is elected through elections (Elected Official), here the governor is the regional head. M. Guntur Hamzah mentioned that the officials elected through elections (Elected Official) are the President, Vice President, DPR, DPD, DPRD, Governor/Deputy Governor, Regent/Deputy Regent, Mayor/Deputy Mayor. The Maslahah perspective views the concept of Ellected Official as being categorized as Maslahah Tahsiniyyah. Maslahah Tahsiniyyah to complete human life. The benefits of Tahsiniyyah need to be fulfilled to provide peaceKeyword : Constitutional Court Decision, Elected Official, Maslahah